Selecting Steady and Transient Photocurrent Response in BaTiO3 Films. (8th July 2015) - Liu, Fanmao; Fina, Ignasi; Gutiérrez, Diego; Radaelli, Greta; Bertacco, Riccardo; Fontcuberta, Josep
Abstract : The ferroelectric polarization and short‐circuit photocurrent in BaTiO3 thin films are studied for different contact configurations that allow to measure the photoresponse and polarization under the presence of large or negligible imprint field. It is found that in all cases, the direction of the photocurrent is dictated by the depolarizing field and ultimately by the film polarization, with a negligible contribution of the imprint electric field. However, dramatic differences are found in their time‐dependent photoresponse. Whereas in presence of imprint, steady photocurrents are observed under suitable illumination, transient photocurrents are generated in absence of imprint. It is argued that this distinct behavior is determined by the different Schottky barrier height at electrodes which thus offers a simple way to tune the film photoresponse. These findings can be exploited for electro‐optic read‐out and writing of ferroelectric memories. Abstract : Steady or transient photocurrents can be obtained on‐purpose in a ferroelectric Pt/BaTiO3 /La2/3 Sr1/3 MnO3 epitaxial heterostructure by selecting the appropriate electrode configuration. The effects of the ferroelectric imprint and depolarizing electric fields on the sign, magnitude, and time dependence of the photoresponse are disentangled.